Effect of Performance Feedback on Turnover Intention through Work Engagement among Indonesian Gen-Z Workers: A Bayesian Structural Equation Modeling Analysis - Moh. Fachri Zahdy; Debora Eflina Purba (Greenation Publisher & Yayasan Global Research National, 2026)
Turnover intention among Generation Z (Gen-Z) is a prominent retention challenge in Indonesia, and the supervisory feedback environment is thought to be one of the levers that can curb it. This study aims to examine whether work engagement mediates the relationship between performance feedback and turnover intention among Indonesian Gen-Z workers. A quantitative cross-sectional design was used with n = 68 workers (aged 18 to 28 years, tenure of 6 to 24 months) screened from 102 respondents. Performance feedback was measured with the Feedback Environment Scale, work engagement with the Utrecht Work Engagement Scale-9, and turnover intention with the Turnover Intention Scale. The latent mediation model was estimated using Bayesian Structural Equation Modeling (the blavaan package) with three Markov chain Monte Carlo chains, 3,000 burn-in iterations, 10,000 post-burn-in iterations, and weakly informative priors. All parameters converged (PSRF ≤ 1.003; minimum effective sample size of 1,073). Performance feedback positively predicted work engagement (a = 0.33; 95% credible interval [0.05; 0.57]), work engagement negatively predicted turnover intention (b = -0.47; [-0.68; -0.22]), while the direct path was not credible (c = -0.24; [-0.48; 0.02]). The standardized indirect effect was -0.15 ([-0.31; -0.02]; HDI [-0.30; -0.02]) with a posterior probability of P(effect < 0) = 0.988, indicating a pattern consistent with full mediation by work engagement. This inference was robust to prior variation. Exact fit was rejected (PPP = 0.008), and the results are reported transparently. Organizations are advised to build a constructive feedback environment to retain Gen-Z talent.